Ceftaroline activity on certain respiratory tract and wound infection agents at the minimum inhibitory concentration level - Keramettin Yanik; Emin Guluzade; Kemal Bilgin; Adil Karadag; Cafer Eroglu; Asuman Birinci; Murat Gunaydin (Journal of Infection in Developing Countries)
Introduction: The aim of this study was to investigate the effectiveness of ceftaroline against agents frequently isolated from respiratory tract and wound infections. Methodology: The study included a total of 250 strains isolated from various clinical specimens, among which were Streptococcus pyogenes, Streptococcus agalactiae, Streptococcus dysagalactiae, Streptococcus pneumoniae, Haemophilus influenzae, and Moraxella catharralis. The bacteria were identified using the matrix-assisted laser desorption/ionization time-of-flight method and conventional methods. The bacteria’s antibiotic susceptibility was tested using appropriate broth microdilution. Mueller-Hinton broth with 4% lysed horse blood, Haemophilus test medium broth, and Mueller-Hinton broth were used. Ceftaroline fosamil results at the minimum inhibitory concentration (MIC) were evaluated using Clinical and Laboratory Standards Institute (CLSI) criteria. For quality assurance, E. coli ATCC 35218, S. aureus ATCC 29213, S. aureus ATCC 43300, S. pneumoniae ATCC 49619, H. influenzae ATCC 49766, H. influenzae ATCC 10211, and H. influenzae ATCC 49247 standard strains were used. Results: According to CLSI criteria, resistance was not detected in any strains. Due to the absence of CLSI criteria for M. catharralis, the susceptibility state for this bacterium was not evaluated. The various strains’ MIC50–MIC90 values were as follows: for S. pyogenes, 0.015–0.06; for S. agalactiae, 0.03–0.125; for S. dysagalactiae, 0.03–0.06; for S. pneumoniae, 0.06–0.125; for H. influenzae, 0.015–0.125; and for M. catharralis, 0.5–1. Conclusions: The results indicate that ceftaroline is quite effective against bacteria that are frequently isolated from respiratory tract and wound infections.